SPORT PSYCHOMETRY, PARTICIPANTS AND INVARIANCE: A CRITICAL REVIEW - Flávio Rebustini; Marcos Alencar Abaide Balbinotti; Renata Eloah de Lucena Ferretti-Rebustini; Afonso Antonio Machado (Journal of Physical Education)
ABSTRACT This article presents a critical review of how sporting context variables and participants may affect the validity evidence of measurement instruments. Despite the literature presenting, there is significant effect of gender, age, practice time, length of experience, sporting experience, stages, training loads, competition, as well as socioeconomic and educational level, among other psychological variables, little has been explored about such effects. Recurrent studies have basically reported age, gender and sport. The absence of control of this information in the sporting context and the participant can cause measurement inaccuracy, limitation in application, errors in interpretations and inappropriate interventions, loss of reproducibility and limitations in comparative studies. Furthermore, it prevents analysis of invariance, compromising their stability. Thus, it is urgent and mandatory to tighten the range of indicators that characterize the participants and the context of studies in sports.